Configuring Check Point NGX VPN-1/fire wall- - Stephens, Robert; Stiefel, Barry J.; Watkins, Stephen (Information security professional) (Rockland, MA : Syngress Pub., 2005)
Check Point NGX VPN-1/Firewall-1 is the next major release of Check Point's flagship firewall software product, which has over 750,000 registered users. The most significant changes to this release are in the areas of Route Based VPN, Directional VPN, Link Selection & Tunnel Management, Multiple Entry Points, Route Injection Mechanism, Wire Mode, and SecurePlatform Pro. Many of the new features focus on how to configure and manage Dynamic Routing rules, which are essential to keeping an enterprise network both available *and* secure. Demand for this book will be strong because Check Point is requiring all of its 3rd party developers to certify their products for this release. * Packed full with extensive coverage of features new to the product, allowing 3rd party partners to certify NGX add-on products quickly * Protect your network from both internal and external threats and learn to recognize future threats * All yuou need to securly and efficiently deploy, troubleshoot, and maintain Check Point NXG.
1: FW-1 NGX Operational changes 2: SmartClients and SmartManagement 3. Management Portal 4: Advanced Authentication 5: Advanced VPN Concepts and Tunnel Monitoring 6: Advanced VPN Client Installations 7: Multicast Security 8: Advanced DoS Protection 9: High Availability and Clustering 10: SecurePlatform 11: Management High Availability & Failover 12: Integration and configuration of CVP / UFP 13: SecureClient Packaging Tool 14: SmartDefense 15: SmartUpdate 16: Performance Pack 17: User Authority 18: Thin Client Support 19: Firewall Troubleshooting.
Includes index.
Keywords: Computer networks -- Security measures; Firewalls (Computer security); Electronic books